Transforming mustahiq into muzzaki through strategic management: An empirical study of productive zakat distribution in Yogyakarta, Indonesia - Iswanaji, Chaidir; Anwar, Syamsul; Hanafi, Syafiq Mahmadah (Universitas Islam Indonesia, 2026)
IntroductionPoverty alleviation remains a major development challenge in Indonesia. Zakat, as an Islamic redistributive mechanism, has the potential to function as a productive economic instrument. This study examines a productive zakat distribution model aimed at transforming mustahiq into muzzaki through empowerment and sustainable economic development, based on economic criteria including income, asset ownership, ability to meet basic needs, and fulfillment of the nisab threshold.ObjectivesThe study aims to analyze how productive zakat contributes to socio-economic transformation, identify institutional and managerial factors influencing program effectiveness, and propose an applicable model of zakat distribution that supports mustahiq independence and transition toward muzzaki status.MethodUsing a qualitative descriptive approach and case study design, the research was conducted in several zakat institutions in Yogyakarta, including BAZNAS, LAZISMU, LAZISNU, and Rumah Zakat. Data were collected through in-depth interviews, direct observation, and document analysis involving 55 mustahiq and zakat managers. The data were analyzed using Miles and Huberman’s model of data reduction, display, and verification.ResultsFindings show that productive zakat programs when integrated with planning, mentoring, and monitoring significantly improve beneficiaries’ income, business performance, and self-reliance. The application of management principles (forecasting, organizing, actuating, and controlling) enhances accountability and program impact. However, challenges remain in limited institutional capacity, uneven monitoring, and insufficient long-term evaluation.ImplicationsThe study demonstrates that productive zakat can serve as an investment in human and social capital rather than a short-term relief tool. It highlights the need for strategic management integration and institutional collaboration to ensure sustainability and measurable economic transformation among mustahiq.Originality/NoveltyThis research contributes to Islamic economic scholarship by offering an empirical framework that links productive zakat management with socio-economic empowerment and sustainable development. It advances the understanding of zakat as a transformative instrument that aligns Islamic social finance with modern development management practices.